Penggunaan Aplikasi ClassDojo Sebagai Upaya Peningkatan Pembelajaran Bagi Guru SMP YPK Merauke - Dina Mariana Br Tarigan; Angla Florensy Sauhenda (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
This study aims to describe training in the use of the ClassDojo learning application as an effort to increase learning for YPK Merauke Middle School teachers. This study discusses the training provided to YPK Merauke Middle School teachers to the assistance provided by the team. Implementation of learning using learning applications can increase teacher creativity in conducting learning in class. This, of course, must be carried out by training so that teachers can apply it in the classroom. This research uses descriptive qualitative method as a process in conducting research. This research was conducted at YPK Merauke Middle School by involving YPK Merauke Middle School teachers as training participants. This study uses data collection techniques with the stages of observation, interviews, documentation, and recording